2021
DOI: 10.1186/s12864-021-07862-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and expression patterns of lipid phospholipid phospholipase gene family in Brassica napus L.

Abstract: Background Lipid phosphate phosphatases (LPP) are critical for regulating the production and degradation of phosphatidic acid (PA), an essential signaling molecule under stress conditions. Thus far, the LPP family genes have not been reported in rapeseed (Brassica napus L.). Results In this study, a genome-wide analysis was carried out to identify LPP family genes in rapeseed that respond to different stress conditions. Eleven BnLPPs genes were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Rapeseed is a vital oilseed crop worldwide; however, CS significantly affects its growth and production ( He et al, 2021 ; Mehmood et al, 2021 ; Raza, 2021 ; Raza et al, 2021e ; Su et al, 2021b ). Exogenously applied plant growth regulators (phytohormones, osmolytes, neurotransmitters, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Rapeseed is a vital oilseed crop worldwide; however, CS significantly affects its growth and production ( He et al, 2021 ; Mehmood et al, 2021 ; Raza, 2021 ; Raza et al, 2021e ; Su et al, 2021b ). Exogenously applied plant growth regulators (phytohormones, osmolytes, neurotransmitters, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miRNAs were found to be involved in cuticular wax biosynthesis in Arabidopsis such as trans-acting small interfering RNA (tasiRNA) was involved in CER3 silencing during stem wax production ( Lam et al, 2015 ). Wang Z. et al (2017) and Su et al (2021b) conducted a genome-scale study in Brassica napus and discovered several miRNAs targeting the fatty acid and lipid metabolism enzymes that could regulate the fatty acid synthesis, lipid transport, and metabolism. Later on, Liu et al (2019) proposed that the bna-miR165a-5p ( Brassica napus miRNA) might be involved in the wax biosynthesis process by regulating the putative target BnaA06g40560D gene.…”
Section: Introductionmentioning
confidence: 99%
“…Rapeseed is an allotetraploid crop that practices widespread genome replication and integration activities [49]. However, rapeseed yield is influenced by numerous abiotic pressures, including temperature (cold/heat), high salinity, drought, waterlogging, and heavy metals toxicity [24,27,50]. The generation of ROS in response to normal and stress atmospheres is assessed and scavenged via GPXs, which is considered one of the most effective ROS antioxidant scavenging enzymes [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Rapeseed (Brassica napus L.) is the second most significant oilseed crop and holds a complex genome. Various abiotic stresses meaningfully restrict rapeseed production [24][25][26][27]. To our best knowledge, the GPX gene family has not been documented in rapeseed.…”
Section: Introductionmentioning
confidence: 99%